2001
DOI: 10.4049/jimmunol.166.10.6423
|View full text |Cite
|
Sign up to set email alerts
|

Calreticulin, a Potential Cell Surface Receptor Involved in Cell Penetration of Anti-DNA Antibodies

Abstract: A 50-kDa protein was purified as a potential receptor, using an affinity matrix containing biotinylated F14.6 or H9.3 anti-DNA mAbs derived from autoimmune (New Zealand Black × New Zealand White)F1 mouse and membrane extracts from cells. This protein was identified as calreticulin (CRT) by microsequencing. Confocal microscopy and FACS analysis showed that CRT was present on the surface of various cells. CRT protein was recognized by a panel of anti-DNA mAbs in ELISA. The binding of F14.6 to lymphocytes and Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 50 publications
2
36
0
4
Order By: Relevance
“…The experiments were conducted under serum-free (AIM-V) conditions to exclude any interference by exogenous proteins and peptides. CRT has previously been shown to be expressed on activated T cells (27) and also detected in 75-100% of the T cells in our experiments.…”
Section: The Tsp-1 Binding Site In Crt Triggers T Cell Migration Intosupporting
confidence: 75%
“…The experiments were conducted under serum-free (AIM-V) conditions to exclude any interference by exogenous proteins and peptides. CRT has previously been shown to be expressed on activated T cells (27) and also detected in 75-100% of the T cells in our experiments.…”
Section: The Tsp-1 Binding Site In Crt Triggers T Cell Migration Intosupporting
confidence: 75%
“…The calreticulin (CALR) protein binds to misfolded proteins and has been previously reported to be associated with systemic lupus and other autoimmune disorders through its binding to autoantibodies (46,47) and DNA (48). The F-box and leucine-rich repeat protein FBXL19 is associated with cellular inflammation (pulmonary) through its action as a ubiquitin ligase to target proteins for proteasomal degradation (49).…”
Section: Discussionmentioning
confidence: 99%
“…Madaio and colleagues (18) described a 110-kDa protein identified as myosin 1 that was immunoprecipitated by a murine anti-DNA mAb from rat hepatoma cells. Seddiki (19) reported that a 50-kDa receptor on human lymphocyte cell lines identified as calreticulin may mediate the cellular penetration of some anti-DNA Abs. Most recently, Eilat and coworkers (6) demonstrated that five pathogenic anti-dsDNA Abs isolated from (NZB ϫ NZW)F 1 mice cross-reacted with ␣-actinin, while two mAbs which were nonpathogenic did not.…”
Section: Discussionmentioning
confidence: 99%